A Proposal of a Scenario to Integrate Active Pedagogical Approaches to Teach Scratch in Primary School - Chekour, Mohammed; Zaoui Seghroucheni, Yassine; Aboulkacem, Amina; Hafid, Moulay Mustapha (International Journal of Interactive Mobile Technologies (iJIM), 2023)
In the digital age, people are increasingly connected and frequently use technology in their daily lives. Elementary school students are no exception. They show a great interest in the digital world and especially in games. Scratch gives these students the opportunity to create their own games instead of being passive consumers of these programs. Also, it is a software that allows the development of computational thinking. Thus, to learn programming using Scratch allows students to be actors in their learning which increases their capacity to solve problems. The objective of this work is to propose a pedagogical scenario to teach Scratch to primary school students based on active pedagogical approaches that put the learner at the centre of the teaching-learning process. Once challenged by a problem, students propose solutions. Scratch gives the opportunity to verify the accuracy of the proposed solutions. Accordingly, students try to detect the source of the error and rectify the instructions of their programs. The class, grouped in trios, evaluates the proposed solutions by adopting the "trial and error" method until the desired result is obtained. Therefore, the scenario proposed in this work combines active pedagogical approaches while taking into consideration the nature of the subject taught. Indeed, it aims to make the students fully involved in their learning with the "trial and error" method and to develop their capacities of investigation and problem-solving in a motivating and collaborative environment.